2022
DOI: 10.2147/jaa.s321017
|View full text |Cite
|
Sign up to set email alerts
|

Expert Opinion on Biological Treatment of Chronic Rhinosinusitis with Nasal Polyps in the Gulf Region

Abstract: Chronic rhinosinusitis (CRS) is defined as the inflammation of nose and paranasal sinuses, affecting the patients' quality of life and productivity. Chronic rhinosinusitis with nasal polyps (CRSwNP) is a principal clinical entity confirmed by the existence of chronic sinonasal inflammation and is characterized by anterior or posterior rhinorrhea, nasal congestion, hyposmia and/or facial pressure or facial pain. Several epidemiologic studies have revealed wide variations in the incidence of CRS among regions gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Expert groups and advisory committees from countries of the Gulf Cooperation Council (GCC) support the use of dupilumab in resistant CRSwNP, providing there is an evidence of type 2 inflammation (eg, total IgE ≥100 or serum eosinophils ≥250), impaired quality of life (SNOT-22 ≥40), and, preferably, concomitant asthma. 24 , 25 The present case series found promising outcomes of the dupilumab use in AFRS, as a subset of CRSwNP, among the Saudi population (as part of the Gulf countries ) who met the aforementioned criteria, with no significant adverse events. Future studies on a larger scale should be conducted evaluating the use of biologics in AFRS.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Expert groups and advisory committees from countries of the Gulf Cooperation Council (GCC) support the use of dupilumab in resistant CRSwNP, providing there is an evidence of type 2 inflammation (eg, total IgE ≥100 or serum eosinophils ≥250), impaired quality of life (SNOT-22 ≥40), and, preferably, concomitant asthma. 24 , 25 The present case series found promising outcomes of the dupilumab use in AFRS, as a subset of CRSwNP, among the Saudi population (as part of the Gulf countries ) who met the aforementioned criteria, with no significant adverse events. Future studies on a larger scale should be conducted evaluating the use of biologics in AFRS.…”
Section: Discussionmentioning
confidence: 58%
“…Accordingly, high-quality guidelines and position papers have been implemented to tackle the aforementioned dilemma. 5 , 24 , 25…”
Section: Discussionmentioning
confidence: 99%
“… 24 A study on patient‐reported and practitioner‐reported outcomes for CRS concluded that 3% of responses generated were objective measures, whereas the majority were subjective, thus highlighting that primary outcomes in future reviews should focus on subjective outcomes in rhinosinusitis‐related research. 28 , 45 , 49 …”
Section: Discussionmentioning
confidence: 99%
“… 1 CRS is a clinical syndrome comprising a group of disorders with different phenotypes and degrees of severity. 2 Phenotypically, it is divided into CRS with nasal polyps (CRSwNP) and without (CRSsNP). 1 CRS has a multi-factorial etiology comprising alterations in mucociliary clearance, epithelial cell barrier abnormalities, and tissue remodeling.…”
Section: Introductionmentioning
confidence: 99%
“… 36 The importance of a multi-disciplinary approach has been underscored on a global scale by the European Forum for Research and Education in Allergy and Airway Diseases (EUFOREA) 38 , 39 and adapted by expert panels for various geographical regions, including Northern Europe 36 and the Gulf countries. 2 …”
Section: Introductionmentioning
confidence: 99%